Protágoras y la invención humana de la política. Las condiciones del pacto social en la Atenas democrática (Argos, 2025)
The paper approaches the sophistic conception of society starting from the issue of what is conceptualised with the idea of social contract in modern terms. A special emphasis is given to Protagoras' thought and its relationship with democratic Athens, mainly the myth of the emergence of politics, the doctrine about the political virtue as an attribute of everyone and the working of logos to make that an opinion gets a real existence. Finally, stress is made on the importance of the citizen education as an immanent element to the political practices of the Athenian democracy.
Keywords: social contract; politics; discourse; truth; opinion